GAMBARAN ACTIVE LEARNING DAN CRITICAL THINKING DALAM IMPLEMENTASI PBL PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TARUMANAGARA (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
Problem based learning (PBL) is a student - centered learning method that provides problem for students to discuss together. One of the benefits of PBL is to encourage students to be actively involved in the learning process and stimulates students to think critically. The purpose of this research is to describe active learning and critical thinking ability in medical students of Universitas Tarumanagara. This is a descriptive study with a cross-sectional design that involves 113 medical students. The data were obtained using a questionnaire of Self-Assessment Scale on Active Learning and Critical Thinking (SSACT). The results of this research shows a mean score of 31,05 (5,36) for active learning and 45,17 (5,23) for critical thinking. From the three classes of the academic stage (2017, 2018, 2019), the highest mean scores of active learning and critical thinking were seen in students of class 2019, while the lowest were seen in class 2017. Students of class 2019 got a mean score of 33,00 (5,11) for active learning and 47,26 (5,04) for critical thinking. Meanwhile, students of class 2017 got a mean score of 29,14 (5,19) for active learning and 43,49 (5,03) for critical thinking.Keywords: active learning; critical thinking; problem based learning AbstrakProblem based learning (PBL) adalah metode pembelajaran yang berpusat pada mahasiswa dengan menyajikan sebuah masalah untuk didiskusikan bersama. Salah satu manfaat PBL yaitu mendorong mahasiswa terlibat aktif dalam proses pembelajaran (active learning) dan menstimulasi berpikir kritis (critical thinking). Tujuan penelitian ini untuk mengetahui gambaran kemampuan active learning dan critical thinking pada mahasiswa Fakultas Kedokteran Universitas Tarumanagara tahap akademik. Penelitian ini merupakan penelitian deskriptif dengan desain cross sectional dan melibatkan 113 mahasiswa. Data diambil dengan menggunakan kuesioner Self-Assessment Scale on Active Learning and Critical Thinking (SSACT). Hasil penelitian menunjukkan rerata skor active learning sebesar 31,05 (5,36) dan critical thinking sebesar 45,17 (5,23). Dari tiga angkatan mahasiswa pada tahap akademik (2017, 2018, 2019), rerata skor active learning maupun critical thinking tertinggi tampak pada mahasiswa angaktan 2019, sedangkan yang terendah yaitu angkatan 2017. Mahasiswa angkatan 2019 memiliki rerata skor active learning sebesar 33,00 (5,11) dan critical thinking 47,26 (5,04). Sedangkan mahasiswa angkatan 2017 memiliki rerata skor active learning sebesar 29,14 (5,19) dan critical thinking 43,49 (5,03).